Lipaemia retinalis in a 29-day-old infant with type 1 hyperlipoproteinaemia. - Hayasaka, S. (1985)
A 29-day-old infant born of consanguineous parents had type 1 hyperlipoproteinaemia associated with lipaemia retinalis. Biochemical analyses disclosed hypertriglyceridaemia, hyperchylomicronaemia, and lipoprotein lipase deficiency. Ophthalmoscopically all retinal vessels had the creamy appearance of lipaemia retinalis. The plasma lipoprotein levels and fundus condition became normal after her ingestion of fat was limited. To our knowledge this is the youngest patient reported with type 1 hyperlipoproteinaemia associated with lipaemia retinalis.